Knowledge of and Attitudes Toward Perinatal Home Visiting in Women with High‐Risk Pregnancies. (1st February 2021) - Barkin, Jennifer L.; Bloch, Joan Rosen; Smith, Katherine E.R.; Telliard, Sarah N.; McGreal, Analise; Sikes, Chris; Ezeamama, Amare; Buoli, Massimiliano; Serati, Marta; Bridges, Christy C.
Abstract : Introduction: Published research indicates that some perinatal home visiting programs are highly effective. However, there is a dearth of information regarding how these services apply to women experiencing a high‐risk pregnancy. The aim of this study was to determine the potential acceptability of home visiting services within this vulnerable population and identify what services women want. Methods: Four focus groups (N = 32) were conducted with a population of low‐income, pregnant individuals in medically underserved central Georgia (United States). Participants were evaluated based on their current exposure to home visiting, receptiveness to home visiting, and reasons for apprehension regarding home visiting. Results: The results of this study were mixed, with women expressing both interest in and reluctance about home visiting programs. Themes of distrust and fear of judgment or persecution existed. Women also varied with regard to what home visiting services they would like offered. Those discussed included assistance with maternal or infant medical needs, maternal function tasks, household tasks, and child care. Discussion: Home visiting programs can be effective for improving maternal and child health outcomes. However, not all home visiting programs effectively reach their target population. More research is needed to determine what women who have high‐risk conditions during pregnancy want help with and how to increase receptiveness. The results of this study could be informative to health care providers who treat persons with high‐risk conditions in identifying adjunctive services for those in need of additional support.